Determination of the Height of Overburden Water-Conducting Fracture Zone in 215102 Working Face of Yue Nan Coal Mine. (12th November 2022) - Chen, Xiangjun; Huang, Zhen; Wang, Lin; Dong, Xiaozhen; Cui, Pengfei
Abstract : In order to extract gas accurately in Yue Nan coal mine and prevent gas over limit and gas accidents, a combination of theoretical analysis and numerical simulation was used to investigate the height of the overburden caving zone and fracture zone in the working face, using 215102 working face as the engineering background. The results show three key strata in the 215102 working face, namely siltstone, sandy mudstone, and sandy mudstone. The empirical formula's calculation results are in good accord with the findings of the theoretical analysis, which indicates that the height of the water-conducting fracture zone created by mining in 215102's working face is 87.35 m. The plastic zone, stress distribution and displacement variation of the model overburden of the working face were analyzed separately in the numerical simulation. The results of the plastic zone simulation show that the caving zone's maximum height is about 15.96 m, and the fracture zone's maximum height is approximately 82.39 m. The stress distribution shows that the caving zone's greatest height is around 13.65 m, while the fracture zone's maximum height is roughly 77.24 m. The amount of overburden subsidence proves that the caving zone's maximum height of about 10.08 m, and the fracture zone's maximum height of approximately 82.69 m. The height of the overburden caving zone and fracture zone of 215102 working face are ultimately found to be 14.02 m and 76.42 m, respectively, based on theoretical analysis, empirical formula calculation, and numerical simulation findings.